2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6089895
|View full text |Cite
|
Sign up to set email alerts
|

Novel flexible dry PU/TiN-multipin electrodes: First application in EEG measurements

Abstract: Dry biosignal electrodes for electro-encephalography (EEG) are an essential step for realization of ubiquitous EEG monitoring and brain computer interface technologies. We propose a novel electrode design with a specific shape for hair layer interfusion and reliable skin contact. An electrically conductive Titanium-Nitride (TiN) thin layer is deposited on a polyurethane substrate using a multiphase DC magnetron sputtering technique. In the current paper we describe the development and manufacturing of the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 9 publications
2
22
0
Order By: Relevance
“…The power increases for lower frequencies for all electrodes. For frequencies below 3 Hz, an increase toward higher values is perceivable in the plasma treated dry MP electrodes, which should be attributed to slightly increased drift behavior, which was already observed in previous studies …”
Section: Chemical Analysis Of the Plasma Activated Pu Surfacessupporting
confidence: 79%
See 1 more Smart Citation
“…The power increases for lower frequencies for all electrodes. For frequencies below 3 Hz, an increase toward higher values is perceivable in the plasma treated dry MP electrodes, which should be attributed to slightly increased drift behavior, which was already observed in previous studies …”
Section: Chemical Analysis Of the Plasma Activated Pu Surfacessupporting
confidence: 79%
“…Moreover, incorrect and/or uncomfortable skin contact may arise due to the stiff nature of some of the proposed base materials (aluminium, [3] steel, [11,12] silicon, [13,14] titanium, [15] and polycarbonate [16] ), and designspecific conceptual problems (micro-needle electrodes [13,14] and rigid planar plates/disks unable to interfuse the hair layer [15,16] ). Hence, in order to reduce some of the referred drawbacks, several authors focused not only on the development of new electrode designs, which allow an effective hair interfusion, [17][18][19][20] but also on the use of more compliant base materials, such as textiles [21] and, above all, flexible polymers. [22][23][24][25] Thermoplastic polyurethanes (TPU) have been extensively applied in several fields that range from technical coatings to biomedical applications, [26][27][28] due to their excellent balance between mechanical properties (high flexibility, dependent on the composition), chemical barrier behavior, soft tact, and biocompatibility, [29,30] thus being appropriate to be used as biopotential electrode base material.…”
Section: Introductionmentioning
confidence: 99%
“…), the authors recently explored the sputtering viability of Ag x :TiN coatings (with close-stoichiometric TiN) by optimizing their deposition parameters and properties [22,23], architecture [24] and electrochemical behaviour [25] on classic substrates (glass and silicon), so that they can be later sputtered onto flexible polymer-based substrates. Preliminary investigations by the authors demonstrated that the use of flexible polymer electrodes with nanocoatings of electrically conductive TiN x allowed for comfortable dry EEG recording, providing signal quality comparable to conventional Ag/AgCl wet electrodes [26], although the coatings displayed a low mechanical stability. Silver was then added to TiN in order to tailor several properties of the matrix (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The specific shape is capable of interfusing the hair layer and enabling stable contact with the scalp. In a preliminary test on a single volunteer a titanium nitride (TiN) coated MP electrode proved to provide Ag/AgCl-comparable signal quality [10]. In the current paper a further comparison of two different titanium (Ti) and TiN coated MP electrodes as well as a conventional Ag/AgCl reference electrode is performed in terms of electrode-skin interfacial impedance and EEG signal quality in of a multi-volunteer study.…”
Section: Introductionmentioning
confidence: 99%